Peran Aparat Penegak Hukum dalam Penerapan Restorative Justice terhadap Tindak Pidana Anak di Indonesia - Ichsan Izzul Hag; Yana Sukma Permana (Decisio: Jurnal Ilmiah Hukum, 2025)
Restorative justice is a legal approach that prioritizes rehabilitation over punishment, particularly in cases involving juvenile offenders. In Indonesia, law enforcement officers play a crucial role in implementing restorative justice, yet various structural and cultural barriers hinder its effectiveness. Despite the existence of supporting regulations, challenges such as inadequate legal awareness, limited resources, and retributive legal culture persist. Addressing these issues is essential to ensure a fair and rehabilitative juvenile justice system. This study employs a qualitative method with a normative legal approach, focusing on regulatory analysis and legal interpretation. Data collection is conducted through comprehensive literature studies, including primary, secondary, and tertiary legal materials. The findings indicate that law enforcement officers act as key facilitators in restorative justice, but their limited training and institutional support hinder optimal implementation. The study also reveals that public perception still leans toward punitive measures, reducing the acceptance of restorative approaches. Strengthening legal frameworks, improving law enforcement training, and enhancing public awareness are necessary steps to overcome these barriers. A collaborative effort between the government, legal institutions, and society is crucial to fully realize the potential of restorative justice for juvenile offenders in Indonesia.